Keluarga dengan Balita Stunting di Kecamatan Kepanjen Kabupaten Malang: Family with Stunting Toddler in Kepanjen District Malang Regency - Sari, Wyssie Ika (Jurnal Surya Medika (JSM), 2022)
Stunting occurs early in life, affecting growth and development and describing chronic malnutrition status. The purpose: to determine the description of families with stunting toddlers. The design: descriptive with a cross-sectional approach. The number of samples is 110 respondents with a simple cluster technique. The inclusion criteria: family with stunting toddlers aged 3-5 years did not experience mental disorders as exclusion criteria. Variables: the number of family members, education, mother's knowledge, income, feeding pattern, history of exclusive breastfeeding, sanitation. Univariate analysis: categorical data used percentage and frequency distribution, while mean, median, min-max, and standard deviation were used for numerical data. This study showed the results: most toddlers (71.8%) had a small number of members, most of the parents (55.4%) had low education, 92.7% of families had a good income, 92.7% of mothers had good knowledge, most toddler (97.3%) have inappropriate feeding pattern, as many as 70% of a toddler have a history of insufficient exclusive breastfeeding, 100% of respondent have good personal hygiene. One of the risk factors for families with stunting toddlers is education which has a role in intake nutrition and parenting. In addition, risk factors in feeding patterns and a history of exclusive breastfeeding have a role in growth and development.